KEABSAHAN JUAL BELI DI BAWAH TANGAN ATAS TANAH BERSETIPIKAT (STUDI KASUS PERKARA No 305/ Pdt G/ 2009/ PN Smg) - Marindi Cintyana, Marindi Cintyana, Endang Sri Santi, R Suharto (Diponegoro Law Journal, 2012)
Indonesian land law based on customary law. It is found in article 5 of the Basic Agrarian Law. According to applicable regulations, land transfer must be done in front of the Land Deed Officer but, in the real life there are still a lot of land transfer was not done in accordance with its regulations, so it would be detrimental to the buyer, because he can only control the rights to the land physically alone while legal ownership of land is still in the name of set forth in the certificate of land. The method used in this research is a method of juridical sociological research conducted by the research literature as well as field research where the main sources obtained from literature sources and interviews with legal scholars and those from the Land Office. Specification of research used in this research is descriptive analysis. The type of data used are primary data and secondary data. The method used in this analysis is a qualitative method, by explaining what is contained in the provisions related to the implementation of legislation and regulations. The research was conducted on a case  No. 305 / Pdt. G / 2009 / PN. SMG. The results of this study indicated that the sale and purchase of land without a deed of sale of the Land Deed Officer is binding on the parties all material requirements are met, and to legalize the sale and purchase of the Sale and Purchase Deed made ​​official Deed Land as a condition for registration of transfer rights to do so land. Efforts to do so as the sale and purchase of land without deed sale is the Land Deed Officer by filing a complaint with the Chief District Court local authorities, the lawsuit that the Chairman of the District Court ruled that the sale of land rights is legitimate and based on the decision it gave the power to the buyer as the plaintiff to act on behalf of the seller and act on its own behalf as a buyer, so that the sale and purchase of land rights can be evidenced by the deed of sale and purchase of the Land Deed Officer to immediately registered at the local Land Office.